Ries crater and suevite revisited—Observations and modeling Part II: Modeling. (5th April 2013) - Artemieva, N. A.; Wünnemann, K.; Krien, F.; Reimold, W. U.; Stöffler, D.
Abstract We present the results of numerical modeling of the formation of the Ries crater utilizing the two hydrocodes SOVA and iSALE. These standard models allow us to reproduce crater shape, size, and morphology, and composition and extension of the continuous ejecta blanket. Some of these results cannot, however, be readily reconciled with observations: the impact plume above the crater consists mainly of molten and vaporized sedimentary rocks, containing very little material in comparison with the ejecta curtain; at the end of the modification stage, the crater floor is covered by a thick layer of impact melt with a total volume of 6–11 km3; the thickness of true fallback material from the plume inside the crater does not exceed a couple of meters; ejecta from all stratigraphic units of the target are transported ballistically; no separation of sedimentary and crystalline rocks—as observed between suevites and Bunte Breccia at Ries—is noted. We also present numerical results quantifying the existing geological hypotheses of Ries ejecta emplacement from an impact plume, by melt flow, or by a pyroclastic density current. The results show that none of these mechanisms is consistent with physical constraints and/or observations. Finally, we suggest a new hypothesis of suevite formation and emplacement by postimpact interaction of hot impact melt with water or volatile‐rich sedimentary rocks.